Is it Time to Introduce the “Precision Tutorial System” for Undergraduate? - Piao, Guangchun; Li, Zhiyong; Wang, Ao; Su, Yifei; Li, Gao; Jin, Xuejun; Yuan, Haidan (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: The aim of this study was to investigate the current situation with the undergraduate tutorial system in China from the students’ perspective and to further improve that system for greater developmental benefits. Materials and Methods: We designed a 21-item questionnaire to analyze the current situation with the undergraduate tutorial system. It was administered to freshman, sophomore and junior students taking a pharmacy undergraduate degree. In all, 415 pharmacy students completed the questionnaire. We collected the data and categorized them into 12 groups before subjecting the data to statistical analysis. We identified the common and different points (such as the most popular response options) between female or male students and by university year. Results: In all, 415 pharmacy students completed the questionnaire. We observed many differences in the popular choices between female or male students as well as among students in different university years. Even when the most popular options were the same, there were differences in the proportions between female and male students as well as among students in different years. Conclusion: There were considerable differences with respect to university year, genders and individuals. Regarding the tutorial system, students need help in different ways. We present the notion of the “Precision tutorial system”, whereby tutors should guide students according to the students’ talents and preference as well as analyze and solve their specific problems. We believe it is imperative to introduce such a system.
Keywords: Precision tutorial system; Undergraduate; Questionnaire; Pharmacy students; Individual